Development of Cyclozos Based Catalytic Converter for motorcycles / Mat Rasid Abas and Mohd Zamri Zakaria - Abas, Mat Rasid; Zakaria, Mohd Zamri (2001)
The project work is to design and fabricate Cyclozos Based Catalytic Converter and install it to the KRISS Modenas 110 cc motorcycles. Through this, we have utilized the capabilities of CAD software, which involves the design of the component from simple two-dimensional design systems to sophisticated, integrated three-dimensional design. Besides that we applied all the skills of fabrication include joining, welding, bending, machining, and etc processes to produce this part.